Improved adsorption characteristics data for AQSOA types zeolites and water systems under static and dynamic conditions - Teo, How Wei Benjamin (2017)
In this manuscript, the amount of water vapour uptakes on zeolites (types AQSOA-Z01, Z02 and Z05) under static and dynamic conditions were measured for the temperatures ranging from 298 K to 333 K and pressures up to saturated conditions. These data are fitted with the theoretical isotherms and kinetics equations, which are developed from Langmurian analogy. The experimentally measured isotherms data varying from Henry's region to the saturated pressure are also expressed in pressure–temperature–uptake co-ordinate system for the calculation of the isosteric heat of adsorption. The variations of isosteric heats are ranged from 1 to 1.4 times of the heat of vaporization. The AQSOA type zeolites show type V isotherms. For better understanding of adsorption and desorption processes, the hysteresis behaviours are also investigated.